Proteomic identification of Profilin1 as a corepressor of estrogen receptor alpha in MCF7 breast cancer cells. Issue 14 (12th June 2013) - Kanaujiya, Jitendra Kumar; Lochab, Savita; Kapoor, Isha; Pal, Pooja; Datta, Dipak; Bhatt, Madan L. B.; Sanyal, Sabyasachi; Behre, Gerhard; Trivedi, Arun Kumar
<x xml:space="preserve">Abstract</x> Nuclear receptor coregulators play an important role in the transcriptional regulation of nuclear receptors. In the present study, we aimed to identify estrogen receptor α (ERα) interacting proteins in Tamoxifen treated MCF7 cells. Using in vitro GST‐pull down assay with ERα ligand‐binding domain (ERα‐LBD) and MS‐based proteomics approach we identified Profilin1 as a novel ERα interacting protein. Profilin1 contains I/LXX/L/H/I amino acid signature motif required for corepressor interaction with ERα. We show that these two proteins physically interact with each other both in vitro as well as in vivo by GST‐pull down and coimmunoprecipitation, respectively. We further show that these two proteins also colocalize together in the nucleus. Previous studies have reported reduced expression of Profilin1 in breast cancer; and here we found that Tamoxifen increases Profilin1 expression in MCF7 cells. Our data demonstrate that over expression of Profilin1 inhibits ERα‐mediated transcriptional activation as well as its downstream target genes in ERα positive breast cancer cells MCF7. In addition, Profilin1 overexpression in MCF7 cells leads to inhibition of cell proliferation that apparently is due to enhanced apoptosis. In nutshell, these data indicate that MS‐based proteomics approach identifies a novel ERα interacting protein Profilin1 that serves as a putative corepressor of ERα functions.